1973
DOI: 10.1002/1097-0142(197303)31:3<746::aid-cncr2820310339>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival in malignant pheochromocytoma of the organ of zuckerkandl with pharmacological treatment

Abstract: An 11‐year follow‐up of a patient with malignant pheochromocytoma of the organ of Zuckerkandl (M.P.O.Z.) is reported. The long survival was probably due to treatment by α and β blocking agents, preventing a cardiovascular catastrophy. The patient ultimately succumbed to diffuse metastatic spread. Radiologic and cytotoxic treatment did not have any appreciable effect on the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The behavior of malignant pheochromocytomas is highly variable but the average survival period after detection of metastases was given as only 3 years in a study reported in 1961 [27]. More recent reports indicate a longer survival [11, [24][25][26]281 as is the case with our patients. Death from recurrent and malignant pheochromocytomas frequently arises from some cardiovascular or cerebrovascular event due to high circulating catecholamine, rather than from tumor growth.…”
Section: Discussionsupporting
confidence: 61%
“…The behavior of malignant pheochromocytomas is highly variable but the average survival period after detection of metastases was given as only 3 years in a study reported in 1961 [27]. More recent reports indicate a longer survival [11, [24][25][26]281 as is the case with our patients. Death from recurrent and malignant pheochromocytomas frequently arises from some cardiovascular or cerebrovascular event due to high circulating catecholamine, rather than from tumor growth.…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, evidence began to accumulate, paving the potential use (reposition) of propranolol as an antitumor drug. This use is supported by several case reports [ 9 , 10 , 11 , 12 ] that postulated the use of propranolol in a rare tumor-like pheochromocytoma to reduce hypertension generated by catecholamines’ secretion. Interestingly, these studies outlined (but did not relate) the absence of metastases and tumor growth amelioration without noticeable side effects, together with the normalization of the heart rate and blood pressure.…”
Section: Why Propranolol?mentioning
confidence: 64%
“…The effect of various treatments including chemotherapy on bone metastasis has not been completely satisfactory (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%